Recommendations for cerebrospinal fluid Alzheimer's disease biomarkers in the diagnostic evaluation of mild cognitive impairment. Issue 3 (27th October 2016) - Herukka, Sanna-Kaisa; Simonsen, Anja Hviid; Andreasen, Niels; Baldeiras, Ines; Bjerke, Maria; Blennow, Kaj; Engelborghs, Sebastiaan; Frisoni, Giovanni B.; Gabryelewicz, Tomasz; Galluzzi, Samantha; Handels, Ron; Kramberger, Milica G.; et al.
Abstract: This article presents recommendations, based on the Grading of Recommendations, Assessment, Development, and Evaluation method, for the clinical application of cerebrospinal fluid (CSF) amyloid‐β1–42, tau, and phosphorylated tau in the diagnostic evaluation of patients with mild cognitive impairment (MCI). The recommendations were developed by a multidisciplinary working group and based on the available evidence and consensus from focused group discussions for 1) prediction of clinical progression to Alzheimer's disease (AD) dementia, 2) cost‐effectiveness, 3) interpretation of results, and 4) patient counseling. The working group recommended using CSF AD biomarkers in the diagnostic workup of MCI patients, after prebiomarker counseling, as an add‐on to clinical evaluation to predict functional decline or conversion to AD dementia and to guide disease management. Because of insufficient evidence, it was uncertain whether CSF AD biomarkers outperform imaging biomarkers. Furthermore, the working group provided recommendations for interpretation of ambiguous CSF biomarker results and for pre‐ and post‐biomarker counseling.